The Difficulties and Anxiety Of 9th-Grade Students in Facing Final Exam During a Pandemic - Lintang Ega Shavira; Sumbaji Putranto (JRPM (Jurnal Review Pembelajaran Matematika), 2022)
This research aims to explain students’ difficulties in learning mathematics, the factors that cause learning difficulties, and student anxiety in facing school final exams during a pandemic and explain the design of a good mathematics learning system that should be carried out during a pandemic according to the results of this research. This research is descriptive qualitative research that was conducted in one of the junior high schools in the Tangerang district in 2021 with the research sample being 9th-grade students. For getting the data, this research used questionnaires, interviews, and documentation techniques. The result of this study found some of the main problems that happened to students in facing school final exams include students' unpreparedness for online learning, lack of interest in learning in students, lack of understanding of the material, feeling lazy to take part in online learning, difficulties in learning mathematics and the anxiety of students themselves in facing the final school exam. Making a good and comfortable learning system by paying more attention to the mental readiness of students and making teaching materials in the form of audio-visual or video can be one of the right solutions. In addition, face-to-face learning can provide motivation to students to increase their confidence. Thus, their anxiety in facing the final school exam can be overcome.